2016
DOI: 10.1037/ser0000086
|View full text |Cite
|
Sign up to set email alerts
|

Self-stigma, personality traits, and willingness to seek treatment in a community sample.

Abstract: Stigma has received attention as a major barrier toward effective mental health service delivery, and previous research has demonstrated that the Five-Factor Model (FFM) domain of Openness to Experience is negatively correlated with stigmatized views of mental health. However, a lack of established relationships between personality and self-stigma, as well as how these concepts affect an individual's treatment-seeking intentions, has left a gap in the literature. To address this, our study recruited a low-inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 49 publications
(89 reference statements)
4
20
0
2
Order By: Relevance
“…This study consistently found the same results as shown in the recent study by Ingram et al (2016), which also revealed the relationships between agreeableness and openness to experience and mental health treatment among Americans. This could be a result of less stigmatized beliefs toward treatment for mental illness, as Brown (2012) revealed that individuals with agreeableness and openness to experience traits were less likely to have stigmatized beliefs toward mental illness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study consistently found the same results as shown in the recent study by Ingram et al (2016), which also revealed the relationships between agreeableness and openness to experience and mental health treatment among Americans. This could be a result of less stigmatized beliefs toward treatment for mental illness, as Brown (2012) revealed that individuals with agreeableness and openness to experience traits were less likely to have stigmatized beliefs toward mental illness.…”
Section: Discussionsupporting
confidence: 91%
“…O’Connor, Martin, Weeks and Ong (2014) showed that self-efficacy and extraversion were associated with intention to seek help among Australians. Most recently, Ingram, Lichtenberg and Clarke (2016) found a relationship between agreeableness and openness to treatment among primary health care users in America.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, Asian American college students who showed stronger adherence to conservation values (i.e., Asian cultural values, such as humility and conformity) reported fewer positive attitudes and a lower willingness to seek psychological help (e.g., Kim, 2007; Shea & Yeh, 2008). Higher levels of the personality trait of openness to experience, which has been linked to the value of openness to change (Roccas, Sagiv, Schwartz, & Knafo, 2002), were associated with lower mental illness-related public stigma (Brown, 2012; Ingram et al, 2016) in college student samples. Given the indirect as well as mixed evidence linking values on the openness to change and conservation axis and help-seeking stigma, we explored these relationships.…”
Section: Values and Stigma Associated With Psychological Help-seekingmentioning
confidence: 99%
“…When a person is aware of and agrees with society’s negative stereotypes related to seeking psychological help (public stigma), particularly when they apply those stereotypes to themselves (self-stigma), a person is more likely to hold negative attitudes about psychological help, avoid acquiring relevant treatment information, and avoid taking steps toward recovery (Corrigan, Larson, & Rüsch, 2009; Lannin, Vogel, Brenner, Abraham, & Heath, 2016; Lannin, Vogel, Brenner, & Tucker, 2015). To tailor intervention efforts to address the underutilization of psychological help, it is important to understand individual differences such as personal values and cultural factors (e.g., race/ethnicity) that contribute to stigmatization (Brown, 2012; Ingram, Lichtenberg, & Clarke, 2016). University students are in the middle of an important developmental period where they are internalizing their social identities as values (Gecas, 2000).…”
mentioning
confidence: 99%
“…Although research suggests that some therapeutic modalities are more effective than others in ameliorating specific types of symptoms, findings are less clear when patient characteristics beyond diagnosis, symptomatology and symptom severity are considered . Personality traits, styles and disorders may moderate treatment seeking behaviour and treatment outcome for certain presenting problems, but inconsistent findings have emerged in this area as well. One personality type, which seems to be particularly important with respect to therapeutic outcome, is dependency.…”
Section: Dependency In Psychotherapymentioning
confidence: 99%